2006
DOI: 10.1111/j.1530-0277.2006.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Energy Drink Ingestion on Alcohol Intoxication

Abstract: Even though the subjective perceptions of some symptoms of alcohol intoxication were less intense after the combined ingestion of the alcohol plus energy drink, these effects were not detected in objective measures of motor coordination and visual reaction time, as well as on the breath alcohol concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
234
2
18

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(262 citation statements)
references
References 39 publications
(38 reference statements)
8
234
2
18
Order By: Relevance
“…Drinkers who believe that caffeine neutralizes the depressive effects of alcohol may expect that by consuming CaffAlc, they can safely tolerate greater quantities of alcohol without impairment. Individuals who consume CaffAlc may have difficulty judging their level of intoxication, 16,17 leading them to drink more alcohol and to engage in more risky behaviors (e.g., driving under the influence).…”
Section: Introductionmentioning
confidence: 99%
“…Drinkers who believe that caffeine neutralizes the depressive effects of alcohol may expect that by consuming CaffAlc, they can safely tolerate greater quantities of alcohol without impairment. Individuals who consume CaffAlc may have difficulty judging their level of intoxication, 16,17 leading them to drink more alcohol and to engage in more risky behaviors (e.g., driving under the influence).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologically, caffeine enhances perceived stimulation and reduces the lethargy often associated with drunkenness, 31 allowing the user to remain wakeful and alert through a longer, heavier drinking episode. Its coadministration with alcohol also diminishes subjective intoxication 32,33 and distorts estimates of alcohol intake.…”
mentioning
confidence: 99%
“…consistent with evidence of a priming effect shown in the laboratory [16]), or whether heavier use and lengthy drinking duration promotes subsequent energy drink use [10]. Assessments of subjective intoxication could also be collected and tested in relation to actual or estimated BACs, confirming laboratory evidence that consumption of AmEDs contributes to underestimates of actual intoxication [1]. Moreover, a within-subjects design with data collected within individuals across multiple drinking occasions would allow for a more powerful analysis, controlling for unmeasured individual characteristics, such as sensation-seeking and risk-taking propensity, which have been found to be related consistently to AmED use [17][18][19].…”
mentioning
confidence: 59%
“…The experimental literature has shown that energy drinks enhance stimulation and lessen the sedating effects of alcohol [1,2], but they do not appear to counteract the impairing effects of alcohol on psychomotor performance [1,3]. With evidence that people who consume alcohol mixed with energy drinks (AmEDs) tend to underestimate how intoxicated they really are [1,4], there is growing concern among alcohol researchers and public health advocates that AmED consumers are drinking alcohol at a faster pace and over a longer period of time, resulting in higher levels of intoxication and a greater likelihood of alcohol-related harm.…”
mentioning
confidence: 99%
See 1 more Smart Citation